2013
DOI: 10.1068/c12172
|View full text |Cite
|
Sign up to set email alerts
|

Innovations for Enabling Urban Climate Governance: Evidence from Mumbai

Abstract: Climate change is a 'wicked' problem. No central authority manages climate change, and those creating the problem are also trying to solve it. Climate change brings uncertainty in ways that cities have not tackled previously. There is a need to explore new governance forms able to deal with change and to enable transformations. In this paper we explore seven local climate innovations to better understand the enabling conditions underpinning success and the governance barriers that are encountered. We connect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Rather, the point is to acknowledge and try to understand their co-existing role, while recognising the complexities of relying on informality and interpersonal ties, especially in the context of climate change pressures where they appear to be playing an increasingly important role. Climate change is a wicked problem that requires messy solutions [36]. There is thus a need to rethink traditional modes of governance and encourage experimental and collaborative ventures through shadow systems and other aspects of institutional architecture.…”
Section: Challenges Of Negotiating the Invisible Aspects Of Climate Cmentioning
confidence: 99%
“…Rather, the point is to acknowledge and try to understand their co-existing role, while recognising the complexities of relying on informality and interpersonal ties, especially in the context of climate change pressures where they appear to be playing an increasingly important role. Climate change is a wicked problem that requires messy solutions [36]. There is thus a need to rethink traditional modes of governance and encourage experimental and collaborative ventures through shadow systems and other aspects of institutional architecture.…”
Section: Challenges Of Negotiating the Invisible Aspects Of Climate Cmentioning
confidence: 99%
“…In this regard, a vast body of literature has suggested that innovation in governance is necessary to allow for extended civic/end-user involvement in the administrative environment, in energy systems, and to spur socially innovative and self-organizing initiatives e.g., [20,40,71,72,89,102,[117][118][119]. Furthermore, in light of the challenge to escape carbon lock-in [25], scholars increasingly argue for a governing approach that fosters innovation and experimentation in governing activities for climate change mitigation at different levels and scales [27][28][29][30]109,[120][121][122][123]. According to Bulkeley and Castán Broto, 'climate change experiments' signify "purposive interventions in which there is a more or less explicit attempt to innovate, learn or gain experience" [29] (p. 363) "in order to reconfigure one or more socio-technical system for specific ends and where the purpose is to reduce greenhouse gases or adapt to climate change" [29] (p. 368).…”
Section: The Need For Experimental Meta-governancementioning
confidence: 99%
“…Based on the concept of resilience, there is a strong concern here for governance innovations, experimentation and social learning [21,22]. This is reflected in the resulting spectrum of research subjects and interests, aiming to interpret overall urban transformation dynamics and identify options for steering [58][59][60][61], develop orientation and practical guidance for urban planning and design [62][63][64] or related foresight [65], explain the emergence and impact of local sustainability innovations [66], as well as related lifestyle changes [67]. Overall, these studies coincide in underlining the need for making ecological system functions and services a cornerstone for redefining stakeholder interactions, altering cognitive and normative frameworks and thereby enhancing the self-organizing capacity of SES for sustainability.…”
Section: Studies Of Systemic Change Engaging With the Citymentioning
confidence: 99%
“…Thus, participation, knowledge co-production, learning-by-doing and adaptive governance become necessary cornerstones of urban policy making and planning cf. [58][59][60][61][62][63]66,67].…”
Section: C: Building Adaptive Urban Communities and Ecosystemsmentioning
confidence: 99%